MENINGKATKAN KEMAMPUAN GURU DALAM MEMANFAATKAN LINGKUNGAN SEKOLAH SEBAGAI SUMBER BELAJAR MELALUI PELATIHAN DAN PEMBIMBINGAN PADA GUGUS ASTER TK RAMBAH KAB. ROKAN HULU - ., Nurma (Edu Research, 2017)
One of the recommended ways of learning in KTSP is to bring students 'learning activities closer to the facts of everyday life around students' environment. Utilizing the school environment as a source of learning becomes an alternative learning strategy. The research procedure is using a school action research model developed by Kemmis & Taggart (2000), where in principle there are four stages of activity, planning, action, observation and evaluation and reflecting, . The results obtained there is an increase in the ability of teachers in utilizing the school environment as a source of learning through a training approach and mentoring TK Gugus Aster teachers Kec. Rambah Kab.Rokan Hulu. Increasing the value of TK Gugus Aster teachers in the implementation of learning using the school environment as a source of learning in the first cycle average 63.63%, cycle II 68.17%, while Cycle III the average value is 100%.